MINI SOLAR PANEL PROPS WITH GUIDED INQUIRY MODEL TO IMPROVE SCIENCE LITERACY - Pertiwi, Andini; Maryati, Maryati; Sarina, Sarina; Jumadi, Jumadi; Wilujeng, Insih; Rahmawati, Laifa (JURNAL EDUSCIENCE, 2025)
Purpose – This research aims to find out:  (1) the effectiveness of using mini solar panel props with guided inquiry models to improve students' science literacy, (2) whether there is a difference in the average score of significant improvement in students' science literacy before and after the implementation of mini solar panel props with guided inquiry models, (3) how much the effect size of using mini solar panel props with guided inquiry models to improve students' science literacy.Methodology – This is a pre-experimental study that used a one-group pretest-posttest design. The study population included all students in class VIII of a junior high school in Yogyakarta. The purposive sampling technique was used to select the sample, which included 31 students from class VIII B. The instrument used was a science literacy test, while data analysis was conducted using descriptive and inferential statistics.Findings – The results of the analysis concluded that 1) mini solar panel props with guided inquiry models effectively improve students' science literacy by 0.55 in the medium category, 2) there is a difference in the average score of significant improvement in students' science literacy before and after the implementation of mini solar panel props with guided inquiry models, 3) the implementation of mini solar panel props with guided inquiry models provides an effect size of 2.19 with a huge category on improving science literacy.Contribution - These findings are expected to improve science education by integrating mini solar panel props with guided inquiry models, making science learning more interesting, practical, and relevant to real-world applications.